E-LEARNING BERBASIS MOBILE PADA MATA PELAJARAN BAHASA INGGRIS DI SMPN 19 KOTA JAMBI: Learning Media, Conventional Learning, E-Learning, Tool, Web. - Megawaty, Merti (JURNAL AKADEMIKA, 2019)
Research on E-Learning website at SMP N 19 Jambi conducted to improve cognitive, psychomotor, and affective in the learnning process, specifically in learning English. The learning process has been carried out only in the classroom, there’s nothing learning process after that, with e-learning is an ongoing learning process will occur. This e-learning application designed through the survey of spaciousness process, and adjust with the syllabus and lesson plans, and english test, download content, chat, evaluation, school news. The result of this research is an e-learning school. Researcher hope the next researcher who developed from this research can add features such as alumni data, school data governance.